Pengembangan Aplikasi Pembelajaran Berbasis Audio Matakuliah Pengantar Teknologi Informasi Untuk Mahasiswa Tuna Netra: Pengembangan Aplikasi Pembelajaran Berbasis Audio Matakuliah Pengantar Teknologi Informasi Untuk Mahasiswa Tuna Netra - Septa; Syndhe Qumaruw Syty; Diki Rasapta (Universitas Pamulang, 2025)
This study aims to develop an audio-based learning application for visually impaired students in the Introduction to Information Technology course at Pamulang University. Visually impaired students often struggle to access materials that rely on visual elements. This application replaces these visual elements with audio delivery, allowing students to access and understand the material independently. The ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was used as the development framework, encompassing a systematic process from needs analysis and design to development, pilot implementation, and evaluation. Functionality and user experience tests were conducted to assess the application’s effectiveness. The results, validated through black box testing and user questionnaires, show a high level of acceptance, with 95% of users finding the application effective and 85% rating it as easy to use. The primary challenge during development was ensuring the clear translation of complex visual concepts into audio. This research contributes to inclusive learning technologies and recommends future development to include more interactive features.